Antioxidant Effects of Sophora davidi (Franch.) Skeels on d–Galactose–Induced Aging Model in Mice via Activating the SIRT1/p53 Pathway - Lin, Beibei; Xu, Dingqiao; Wu, Sanqiao; Qi, Shanshan; Xu, Youmei; Liu, Xiang; Zhang, Xiaoying; Chen, Chen (Frontiers in Pharmacology, 2021)
This study investigated the protective effect of Sophora davidi (Franch.) Skeels fruits extract (SDE) on D–galactose–induced acute aging in mice. Ultra performance liquid chromatography coupled with tine-of-flight mass spectrometry (UPLC-Q-TOF/MS) was performed to identify the composition of compounds in SDE. KM mice were divided stochastically into the normal control group (NC, saline), D–galactose (D-gal) model group, vitamin C (Vc) group (positive control), low–, medium– and high–dose SDE treat groups. After 28 days administration and fasting overnight, the serum, liver, and brain samples of mice were collected. The levels of inducible nitric oxide synthase (iNOS), acetylcholinesterase (AChE) activity in the brain, malondialdehyde (MDA) and reduced glutathione (GSH) content, superoxide dismutase (SOD) and total antioxidant capacity (T–AOC) activity in the liver and brain were measured. Immunohistochemistry was applied to detect silent information regulator 1 (SIRT1) and p53 protein expression in the liver and brain, and quantitative real-time Polymerase chain reaction (qRT-PCR) was used to detect the expression of nuclear factor κB (NF–κB), tumor necrosis factor (TNF–α), interleukin–6 (IL–6), interleukin-1β (IL–1β), and anti-aging factor Klotho in the liver and brain. The results showed that UPLC-Q-TOF/MS identified 78 compounds in SDE. SDE could reduce the iNOS activity in serum and AChE activity in the brain, upregulate the levels of SOD, T–AOC and GSH in liver and brain, and debase the MDA content in liver and brain. SDE could downregulate the mRNA expressions of TNF–α, NF–kB, IL–1β, and IL–6 in the liver and brain, and elevate the mRNA expression of Klotho. SDE improved the pathological changes of the liver and brain induced by D–gal, increased the expression of SIRT1 protein in the liver and brain, and inhibited the expression of p53 protein induced by D–gal. To summarize, SDE demonstrated clear anti–aging effect, and its mechanism may be relevant to the activation of the SIRT1/p53 signal pathway.